Controlling the degree of sulfonation and its impact on hybrid cross-linked network based polyphosphazene grafted butylphenoxy as proton exchange membrane. (9th August 2018) - Ouadah, Amina; Luo, Tianwei; Gao, Shuitao; Zhu, Changjin
Abstract: A new hybrid based polyphosphazene backbone is synthesized via a series of reactions (ring opening of polyphosphazene, bromination, grafting groups, Atom transfer radical polymerization (ATRP) and sulfonation) with a controlled degree of sulfonation. The synthesis is proved via the 1 H NMR analysis at different steps. The corresponding membranes were elaborated via a casting method and characterized by 1 H NMR, FTIR, and XPS. Conductivity of the synthesized proton exchange membranes is as good as that of the commercial Nafion and displays at the same time a low swelling ratio and water uptake due to the cross-linking process. The membrane's activation energies are very low confirming the easy transport through the channels. As matter of fact, the morphology study reveals a well hydrophilic/hydrophobic nanophase separation. The present membranes are chemically and thermally very stable, no significant weight loss was observed after the Fenton's reagent test and no thermal degradation occurs at temperatures lower than 250 °C (considered high temperature for nowadays proton exchange membranes). Graphical abstract: Image 1 Highlights: A new hybrid based polyphosphazene backbone is synthesized via a series of reactions. Membranes display better conductivity than Nafion 117. Synthesized membranes exhibit low swelling ratio and water uptake. Morphology study reveals a well hydrophilic/hydrophobic nanophase separation. Membranes are chemically and thermally very stable.